Who Needs Follow-Up after Endoscopic Resection of Colorectal Adenomas? - Belle, Sebastian (Viszeralmedizin, 2014)
BACKGROUND: Surveillance colonoscopy after endoscopic resection of colorectal adenomas is a crucial step in the concept of colorectal cancer screening. After identifying the patients at risk with screening and resection of adenomas, there has to be a tailored surveillance. Surveillance colonoscopy should detect recurrent and metachronal adenomas at a stage where they can be removed endoscopically. In the following, the criteria for a risk-adapted surveillance interval are presented. METHODS: A literature review based on American, European, and German guidelines for surveillance after polypectomy and the German guideline for the diagnosis and treatment of ulcerative colitis, as well as a selective literature search into hereditary colorectal cancer were performed. RESULTS: State of the art surveillance after endoscopic resection of colorectal adenomas is based on a focused anamnesis and the index colonoscopy. On the basis of existing guidelines, a risk-adapted surveillance strategy can be implemented. CONCLUSIONS: Adherence to surveillance guidelines is a basic part of colorectal cancer screening and should be the starting point for further research.